2021
DOI: 10.3390/polym13223887
|View full text |Cite
|
Sign up to set email alerts
|

Anion Exchange Membranes with 1D, 2D and 3D Fillers: A Review

Abstract: Hydroxide exchange membrane fuel cells (AEMFC) are clean energy conversion devices that are an attractive alternative to the more common proton exchange membrane fuel cells (PEMFCs), because they present, among others, the advantage of not using noble metals like platinum as catalysts for the oxygen reduction reaction. The interest in this technology has increased exponentially over the recent years. Unfortunately, the low durability of anion exchange membranes (AEM) in basic conditions limits their use on a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 140 publications
1
7
0
Order By: Relevance
“…Remarkably, the present water phase technique shows improved selectivity due to the uniform distribution of ZIF-8 nanofillers in the polymeric matrix, even at higher concentrations (up to 40.5% of ZIF-8 loadings). The results further confirmed that the aqueous phase method could overcome the nanofiller aggregation problem in the MMMs for high-filler loadings, as compared with solid nanofiller incorporation methods [ 47 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 59%
“…Remarkably, the present water phase technique shows improved selectivity due to the uniform distribution of ZIF-8 nanofillers in the polymeric matrix, even at higher concentrations (up to 40.5% of ZIF-8 loadings). The results further confirmed that the aqueous phase method could overcome the nanofiller aggregation problem in the MMMs for high-filler loadings, as compared with solid nanofiller incorporation methods [ 47 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 59%
“…Progress has been made in addressing the challenges to fuel cell efficiency by considering different operating conditions, utilizing different fuels and components [ 16 , 17 ]. Accordingly, various fuel cells have been termed, such as low- [ 18 ], intermediate- [ 19 ], and high-temperature [ 20 ] proton-exchange membrane fuel cells (PEMFCs) [ 21 , 22 ], alkaline fuel cells [ 23 , 24 , 25 , 26 ], direct methanol fuel cells (DMFCs) [ 27 , 28 ], direct ethanol fuel cells [ 29 ], molten-carbonate fuel cells [ 30 ], direct borohydride fuel cells [ 31 ], solid-oxide fuel cells [ 32 ], unitized-regenerative fuel cells [ 33 , 34 ], and microbial fuel cells [ 35 ]. In recent years, considerable attention has been paid to DMFCs [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been explored to decrease the degradation [18] including a change of the polymer backbone [19,20], the introduction of long side chains, [21][22][23][24], and the delocalization of the positive charge [13,25]. Similarly, the use of composites with stable inorganic materials in alkaline environments such as hydrotalcites have shown an improvement in mechanical properties [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%